Navigating the Digital Frontier: How to Control Your Data in AI Health Apps - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2023)
Navigating the Digital Frontier: How to Control Your Data in AI Health Apps The integration of Artificial Intelligence (AI) into health applications has...
Keywords: Drug Discovery; Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation